Sulfated galactans from red seaweed Gracilaria fisheri target epidermal growth factor receptor (EGFR) and inhibit cholangiocarcinoma cells (CCA) proliferation - Sae-lao, Thannich; Tohtong, Rutaiwan; Bates, David O.; Wongprasert, Kanokpan (World Scientific Publishing, 2017)
Cholangiocarcinoma (CCA) is increasing in incidence worldwide and is resistant to chemotherapeutic agents, making treatment of CCA a major challenge. Previous studies reported that natural sulfated polysaccharides (SPs) disrupted growth factor receptor activation in cancer cells. The present study, therefore, aimed at investigating the anti-proliferation effect of sulfated galactans (SG) isolated from the red seaweed Gracilaria fisheri (G. fisheri) on CCA cell lines. Direct binding activity of SG to CCA cells, epidermal growth factor (EGF) and epidermal growth factor receptor (EGFR) were determined. The effect of SG on proliferation of CCA cells was investigated. Cell cycle analyses and expression of signaling molecules associated with proliferation were also determined. The results demonstrated that SG bound directly to EGFR. SG inhibited proliferation of various CCA cell lines by inhibiting EGFR and extracellular signal-regulated kinases (ERK) phosphorylation, and inhibited EGF-induced increased cell proliferation. Cell cycle analyses showed that SG induced cell cycle arrest at the G0/G1 phase, down-regulated cell cycle genes and proteins (cyclin-D, cyclin-E, Cdk-4, Cdk-2), and up-regulated the tumor suppressor protein P53 and the cyclin-dependent kinase inhibitor P21. Taken together, these data demonstrate that SG from G. fisheri inhibited proliferation of CCA cells, and its mechanism of inhibition is mediated, to some extent, by inhibitory effects on EGFR activation and EGFR/ERK signaling pathway. SG presents a potential EGFR targeted molecule, which may be further clinically developed in a combination therapy for CCA treatment.